The impact of ketamine on cognitive outcomes in geriatric anesthesia: a comprehensive review - You, Shuyong; Li, Zhaohui (Frontiers in Psychiatry, 2025)
BackgroundKetamine, a dissociative anesthetic with N-methyl-D-aspartate (NMDA) receptor blockade, has become increasingly popular in geriatric anesthesia because of its hemodynamic stability, lack of respiratory depression, and possible neuroprotective properties. Yet, its effect on cognitive function in elderly surgical patients is unknown. Postoperative cognitive dysfunction (POCD) and postoperative delirium (POD) are frequent complications in elderly surgical patients, resulting in longer hospital stays, higher healthcare costs, and long-term cognitive impairment. Although there is some evidence to support ketamine in decreasing neuroinflammation and maintaining cognitive function, others describe high risks of delirium and hallucination, especially at higher doses.MethodsThis review assessed the existing literature on ketamine’s impact on cognitive outcomes in older anesthesia. A comprehensive review of randomized controlled trials (RCTs was performed, assessing ketamine’s potential to prevent or worsen POCD and POD.ResultsResults show that low-dose ketamine (0.3–0.5 mg/kg) is neuroprotective and decreases the rate of cognitive dysfunction in certain patients. Nevertheless, findings continue to be at odds because study design, population of patients, dosing schedules, and measure of cognition may differ. Secondly, the weighting of ketamine’s neuroprotective and neurotoxic effects is dose-dependent with larger doses inducing unwanted neuropsychiatric impacts.ConclusionIn light of these divergent results, additional large-scale, multicenter RCTs are needed to establish optimal dosing regimens and to identify elderly patient subgroups that could be treated safely with ketamine to avoid cognitive complications. Multimodal techniques of anesthesia and long-term cognitive outcomes will also need to be studied in future studies to further delineate ketamine’s definitive place in geriatric anesthesia.